The Effects of Covid-19 on the Digital Literacy of the Elderly: Norms for Digital Inclusion - Martínez-Alcalá, Claudia I.; Rosales-Lagarde, Alejandra; Pérez-Pérez, Yonal M.; Lopez-Noguerola, Jose S.; Bautista-Díaz, María L.; Agis-Juarez, Raul A. (Frontiers in Education, 2021)
The current sanitary crisis due to COVID-19 has further evidenced the enormous digital exclusion of older adults. Furthermore, the crisis has urged older adults to adopt new technologies to facilitate their tasks, as well as to provide them with an effective means against loneliness and social isolation caused by the confinement. In light of this, Digital Literacy is necessary for all those excluded from the digital era, who are characterized mainly by little or no ability to effectively use technologies. Nevertheless, detailed studies showing the leap from mixed (Blended Learning, BL) to digital literacy in the elderly have not been published. The objective of the present research was to analyze the level of Digital Literacy with the Digital Literacy Evaluation (DILE) of two groups of elderly adults with different levels of literacy (Group 1: G1, and Group 2: G2) during three stages: BL (Aug-Dec 2019); Transition (Feb-Jun 2020); and Digital (Aug- Dec 2020). Comparisons were made before each educational level (pre-pre-pre) and after each educational level (post-post-post) and during consecutive periods before and after each semester (pre vs post) and throughout different educational levels (G1: Basic 1, B1; Basic 2, B2; and intermediate 1, I1; and G2: Intermediate 1 to 3, I1, I2, & I3). Subsequently, considering all the elderly who had passed at least one of the literacy levels, we worked with a total sample of 176 older adults. The comparisons showed that, before the pandemic, G1’s pre digital literacy levels increased between B1 and B2 and that the differences continued with that increasing trend between the B1 level and the I1 completely digital treatment, and the same was observed for post measurements. On the other hand, for the G2, the differences in the DILE were statistically significant between the pre-condition of I2 (before the pandemic) and the I3 (completely digital treatment); and between the pre-conditions of I1 and I3; the same results were obtained for post treatments. Also, pre vs post scores on the DILE were statistically significant and older adults increased progressively their digital literacy despite the COVID-19 pandemic and jumped to the digital age.